Two new species of Pharaxonothinae beetles (Coleoptera: Erotylidae) inhabiting cones of the cycad Ceratozamia santillanii Pérez-Farr. & Vovides (Cycadales: Zamiaceae) in Mexico - Tang, William; Dominguez, Hector Gomez (Zootaxa, 2022)
Two beetles, Ceratophila (Vovidesa) chipjonesi, new species, and Pharaxonotha perezi, new species, (Coleoptera: Erotylidae: Pharaxonothinae) are described from the male cones of the New World cycad Ceratozamia santillanii Pérez-Farr. & Vovides (Cycadales: Zamiaceae). Morphological analysis and keys are provided for distinguishing these from related beetles inhabiting Ceratozamia in Mexico.